2012
DOI: 10.4103/2229-5151.100893
|View full text |Cite
|
Sign up to set email alerts
|

Quality care in pediatric trauma

Abstract: Infrastructure, processes of care and outcome measurements are the cornerstone of quality care for pediatric trauma. This review aims to evaluate current evidence on system organization and concentration of pediatric expertise in the delivery of pediatric trauma care. It discusses key quality indicators for all phases of care, from pre-hospital to post-discharge recovery. In particular, it highlights the importance of measuring quality of life and psychosocial recovery for the injured child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Children with a strong sense of fear, life threat, and loss of control during or after the unintentional injury have been found to be at higher risk for the development of PTSD (Langeland & Olff, 2008). Additional risk factors in the development of PTSD include female gender, pretrauma psychopathology, perception of threat to life, and posttrauma parental distress (Simpson, Rivara, & Pham, 2012).…”
Section: Asd and Ptsdmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with a strong sense of fear, life threat, and loss of control during or after the unintentional injury have been found to be at higher risk for the development of PTSD (Langeland & Olff, 2008). Additional risk factors in the development of PTSD include female gender, pretrauma psychopathology, perception of threat to life, and posttrauma parental distress (Simpson, Rivara, & Pham, 2012).…”
Section: Asd and Ptsdmentioning
confidence: 99%
“…Studies have shown that 10%-35% of children will experience PTSD after a traumatic event, whereas many more exhibit subclusters of distressing symptoms (Langeland & Olff, 2008). Several studies have suggested that injuries lead to higher risk of PTSD than other serious pediatric medical conditions such as diabetes and cancer (Simpson et al, 2012). Recognizing the magnitude of the risks of PTSD can catapult the members of the trauma team to take preventive action for children at risk.…”
Section: Asd and Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we found existing literature that also contained reviews of QIs in trauma care, such as Stelfox et al, 11 who followed a rigorous methodology, but many of the results were not operative. Pham et al 19 did detail the indicators in greater depth, they were structured in a confusing, less visual way. McCarthy et al 20 analysed trauma care systems and other health outcomes in an appropriately structured way, and the results were published with the prehospital and hospital settings as separate aspects, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, substantial variations in both provision of care and short- and long-term outcome exist between centers and tackling these differences holds great promise to improve TBI management across the continuum of care. Quality indicators by phase of care have been identified in pre-hospital care, in-hospital and post-hospital care as well as family/care-taker burden ( 105 ) and based on these, we propose the desired conditions and the most common areas for improvement to ensure that injured children receive appropriate emergency care ( Table 2 ). This information may inform educational interventions, as well as promote research program development.…”
Section: Short- and Long-term Outcomesmentioning
confidence: 99%